Pengembangan Sistem Filsafat Pancasila - Sudarso, Sudarso (Jurnal Filsafat "WISDOM", 2006)
Pancasila is a system of philosophy, the relation of eachprinciple is hierarchy-pyramidal. Logical consequence of Pancasilaas a philosophical system, therefore, is give basis for the implementation inIndonesian government practiceâ€”economic, culture, law, defend, socialethic, technology, and education system. Pancasila ought to give meaningnot only as â€œThe five principles of ethicâ€, but naturally, Pancasila is â€œThefive principles of Indonesian Nationalityâ€. It is very important tonote that in the nation-state life, Pancasila as national identity mustbe developed in order to make Indonesian people standing parallelwith other peoples in welfare and justice condition. The differenceinterpretation of Pancasila does not make it poor but instead ofmake it powerful as a system of philosophy. Â